Effects of naltrexone on adolescent alcohol cue reactivity and sensitivity: an initial randomized trial. (13th March 2013) - Miranda, Robert; Ray, Lara; Blanchard, Alexander; Reynolds, Elizabeth K.; Monti, Peter M.; Chun, Thomas; Justus, Alicia; Swift, Robert M.; Tidey, Jennifer; Gwaltney, Chad J.; Ramirez, Jason
Abstract Adolescent alcohol use is associated with myriad adverse consequences and contributes to the leading causes of mortality among youth. Despite the magnitude of this public health problem, evidenced‐based treatment initiatives for alcohol use disorders in youth remain inadequate. Identifying promising pharmacological approaches may improve treatment options. Naltrexone is an opiate receptor antagonist that is efficacious for reducing drinking in adults by attenuating craving and the rewarding effects of alcohol. Implications of these findings for adolescents are unclear; however, given that randomized trials of naltrexone with youth are non‐existent. We conducted a randomized, double‐blinded, placebo‐controlled cross‐over study, comparing naltrexone (50 mg/daily) and placebo in 22 adolescent problem drinkers aged 15–19 years (M = 18.36, standard deviation = 0.95; 12 women). The primary outcome measures were alcohol use, subjective responses to alcohol consumption, and alcohol–cue‐elicited craving assessed in the natural environment using ecological momentary assessment methods, and craving and physiological reactivity assessed using standard alcohol cue reactivity procedures. Results showed that naltrexone reduced the likelihood of drinking and heavy drinking (P's ≤ 0.03), blunted craving in the laboratory and in the natural environment (P's ≤ 0.04), and altered subjective responses to alcohol consumption (P's ≤ 0.01). Naltrexone was generally well tolerated by participants. This study provides the first experimentally controlled evidence that naltrexone reduces drinking and craving, and alters subjective responses to alcohol in a sample of adolescent problem drinkers, and suggests larger clinical trials with long‐term follow‐ups are warranted.